INNOVACIÓN EN LA PRODUCCIÓN Y GESTIÓN DE EMPRENDIMIENTOS DE COBAYOS COMO BASE DE LA SEGURIDAD ALIMENTARIA Y DEL BIENESTAR DE LOS SECTORES RURALES DE LAS PARROQUIAS URDANETA, SAN ANTONIO DE CUMBE Y EL TABLÓN DE OÑA, CANTÓN SARAGURO, PROVINCIA DE LOJA, AÑO 2016 - León Jaramillo, Ángel Vinicio (2017)
Although the production of guinea pigs in the Urdaneta, San Antonio de Cumbe and El Tablón de Oña rural parishes of the canton and province of Loja is an economic activity practiced by the heads of household and their families, by tradition or custom, but with very low levels of production and productivity, and with low utility, not doing the same without taking advantage of technical recommendations and practically for self consumption. This is why the research "Innovation in the production and management of guinea pig enterprises as a basis for food security and well-being of the rural sectors of the Urdaneta, San Antonio de Cumbe and El Tablón de Oña parishes, in the canton and province of Loja, year 2016 ". Its general objective was: To determine the current systems of production and management of guinea pig enterprises, practiced by the families of the rural sectors of the Urdaneta, San Antonio de Cumbe and El Tablón de Oña parishes, of the canton and province of Loja, in 2016, through a descriptive study, purpose of elaborating a proposal of innovation in the systems of production and management of guinea pigs that contributes to the food security, the increase of the level of economic income and the fulfillment of the social indicators of human development. Participants in the research were heads of household, farmers and agricultural development officials and parish authorities. The scientific method was used with its modalities: inductive, deductive, analytical, synthetic and statistical. The research techniques were: bibliographic, survey, scientific observation and statistics, supporting the determination of social and economic indicators to measure welfare, the StataMP 13. The main results of the research were: 1) The majority of caviculturists have been practicing this economic activity for years, however, they operate outside the technical recommendations, so their production and productivity are very low, generally earmarking their production to self-consumption and the reinforcement of food sovereignty, guinea pig meat uses for their sustenance other agricultural products that produce them, not working in addition, with business plans or carrying out productive enterprises which is corroborated by the finding that the producers do not carry administrative-accounting processes; and (2) with respect to welfare indicators, it has been found that in the parishes investigated, the minimum recommended for the achievement of well-being is generally not reached; This happened in education: with the net enrollment rate in adolescents, net enrollment rate in basic education, and net enrollment rate in high school; In health: with the infant mortality rate, chronic malnutrition rate in children under 5 years of age, percentage of adolescents aged 15 to 19 years pregnant, full occupancy rate in persons with disabilities, percentage of public institutional childbirth coverage, duration Average exclusive breastfeeding, percentage of children under 5 participating in public child development services, percentage of people with public health insurance; In housing: percentage of households with own dwellings, percentage of households living in housing with inadequate physical characteristics, percentage of households with access to sanitation services, percentage of households with internet access, percentage of households with access to landline, Percentage of households with access to water piped by public network, percentage of households living in overcrowding; In economic indicators: the Gini coefficient of income distribution, Poverty Index for Unsatisfied Basic Needs (NBI), public credit concentration index, unemployment rate for people between 16 and 29 years of age; And, in social indicators: index of renewal of the potentially active population, index of female headship, dependency index, index of children enrolled in the Civil Registry, percentage of the EAP receiving public training for professional benefit and qualification of Satisfaction with life.